Iterative Restoration of the Fringe Phase (REFRASE) for QSM - Lindemeyer, Johannes; Worthoff, Wieland A.; Shymanskaya, Aliaksandra; Shah, N. Jon (Frontiers in Neuroscience, 2021)
In Quantitative Susceptibility Mapping (QSM), reconstructed results can be critically biased by misinterpreted In quantitative susceptibility mapping (QSM), reconstructed results can be critically biased by misinterpreted or missing phase data near the edges of the brain support originating from the non-local relationship between field and susceptibility. These data either have to be excluded or corrected before further processing can take place. To address this, our iterative restoration of the fringe phase (REFRASE) approach simultaneously enhances the accuracy of multi-echo phase data QSM maps and the extent of the area available for evaluation. Data loss caused by strong local phase gradients near the surface of the brain support is recovered within the original phase data using harmonic and dipole-based fields extrapolated from a robust support region towards an extended brain mask. Over several iterations, phase data are rectified prior to the application of further QSM processing steps. The concept is successfully validated on numerical phantoms and brain scans from a cohort of volunteers. The increased extent of the mask and improved numerical stability within the segmented globus pallidus confirm the efficacy of the presented method in comparison to traditional evaluation.